Evaluation of the Antifungal Activity of Five Medicinal Plants on the in vitro Growth of a Multi-resistant Strain of Candida Albicans - Ange, Konan Gbê Kouakou N’dri; Sitapha, Ouattara; Yao, Kanga; Urbain, Monney Yapo; Mathieu, Kra Adou Koffi (European Scientific Journal, ESJ, 2022)
This study was conducted to determine the antifungal potential of plants traditionally used in the treatment of infections. Five (5) plants were collected. The anti-candida albicans activity was evaluated by the double dilution method in tilted tubes with the aqueous and hydroethanolic extracts of the different plants. The results showed that the 70% ethanolic extracts were more active than the aqueous extracts for all plants. The 70% ethanolic extract of T. ivorensis (FMC = 1.56 mg/ml) was the most active on the tested strain. It was followed by T. superba (MFC = 3.125 mg/ml) D. benthamianus (MFC = 50 mg/mL), G. arborea (MFC= 50 mg/mL) and J. secunda (MFC ˃ 50 mg/mL). The phytochemical screening revealed the presence of seven major groups of compounds, among which saponins and catechins are the most abundant in the aqueous extracts. Polyphenols, Flavonoids, Polyterpenes and Sterols as well as Tannins are equally present in the alcoholic and aqueous extracts of the different plants at variable levels. These compounds could justify its activity and its traditional use.